(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The geology of the study area is dominated by limestone rocks with strength (moderately weak to moderately strong) and containing joints that yield easily. Consequently, rockfalls along roadcuts are a major geological hazard. In this study, we performed a rockfall hazard-risk assessment on the three sections of the road expected to have the highest possibility of rockfall. We employed the evaluation criteria of "RHRS" developed by the Federal Highway Administration (FHA). An analysis of roadcuts at 3 ranges concerning geographic and geological conditions resulted in the identification of one class of rockfall hazard (low). slopes were assessed as low class.